The Traditional Gender Conceptions Among Sundanese in Rural Java and its Impact on the Community’s Post-Disaster Management - Shidqi, Fathimah; Abdoellah, Oekan S; Supangkat, Budiawati (Jayapangus Press, 2025)
This study analyzes the traditional gender conceptions within the Sundanese community in Cikembang Village, West Java, explores the factors that shape these conceptions, and examines their impact on the community’s post-disaster management. Indonesia is prone to disasters, especially in West Java, where most of the Sundanese community resides. In 2021, a flash flood disaster occurred in one of the rural areas of West Java, namely in Cikembang Village. Gender as part of the socio-cultural structure influences how communities experience and respond to disasters, therefore, it is very important to study disaster events from a gender perspective. The research method used in this study is qualitative with a case study approach, and the data was collected through in-depth interviews and observations. This study shows that the Sundanese community has traditional gender conceptions, assigning distinct responsibilities to men and women. Men are seen as leaders and providers, while women are expected to nurture and fulfill reproductive roles. These gender conceptions are shaped by socio-cultural values and Islamic religious teachings. The rural context of Cikembang further solidifies the dominance of these traditional gender conceptions. These traditional gender conceptions greatly affect labor division in community post-disaster management. Men's dominance in leadership results in women's underrepresentation in decision-making, minimizing their contributions. It is essential to understand gender dynamics in disasters and recognize women's roles in resilience, as this can reveal how socio-cultural factors influence disaster-related social dynamics.